Identifying the Environmental Strategies in Construction Site for Malaysian Contractors in Johor. Issue 1 (May 2020) - Abidin, N A Z; Ghani, A H A; Mohammad, H
Abstract: The construction industry needs to make a significant positive impact on the environment. Although there were a number of successful initiatives, nevertheless, those initiatives are deemed inadequate. There is evidence of lacking in self-inventiveness in applying the concept of sustainability among local construction contractors. Part and parcel, this shortfall stems from a scarce availability of practical guideline for sustainable methods that can be applied during the construction phase. Thus, research was mooted grounded from the issues identified, and further discusses the environmental strategies in construction sites for Malaysians contractors. Therefore, rooting for qualitative endeavours within the initial stages of the research, in-depth literature analysis and semi-structured interview were conducted respectively. Subsequently, for both undertakings, manual-type of analysis were selected. The former was utilising systematic literature review with multi-layered thematic analysis; meanwhile the latter was embedding a simple themes' agreement analysis. The outcomes from the first stage of research have outlined five (5) main environmental strategies, namely; (1) protection of the natural environment, (2) waste management, (3) reuse and recycle of resources, (4) general site management, and (5) resource consumption. These strategies were further strengthened based on the subsequent interview conducted towards G6 and G7 contractors. Nevertheless, the research also recorded several important points from the open- type questions, which may influence the suggested strategies. Finally, the research proposed for succeeding quantitative stage (i.e. questionnaire surveys) in order to generalise the previous outcomes to a large population of contractors.